2018
DOI: 10.4067/s0717-95022018000300984
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects Against Thioacetamide Induced Liver injury in Rats

Abstract: Potent heptatotoxic chemicals such as carbon tetrachloride and thioacetamide (TAA) are used to evaluate hepatoprotective agents. Here we sought to investigate the potential protective effect of the antidiabetic and antioxidant drug, metformin against liver injury induced by TAA. Model group rats received several injections of TAA (200 mg/kg) before being sacrificed after 10 weeks and the protective group started the treatment two weeks prior to TAA injections and continued receiving both agents, metformin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Additionally, TAA-induced intoxication caused innate antioxidant system impairment, as evidenced by a marked consumption of both brain and liver GSH content while an increase in their MDA content. This observation is in agreement with many earlier studies which proved the TAA-induced lipid peroxidation and oxidative stress effect [ 18 , 32 , 37 ]. In harmony with the current results, a previous study suggested that reactive oxygen species (ROS) produced by TAA induce inflammation via the activation of Nuclear factor kappa B (NF-κB), which subsequently increased the release of downstream proinflammatory mediators such as IL-6 and TNF-α [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Additionally, TAA-induced intoxication caused innate antioxidant system impairment, as evidenced by a marked consumption of both brain and liver GSH content while an increase in their MDA content. This observation is in agreement with many earlier studies which proved the TAA-induced lipid peroxidation and oxidative stress effect [ 18 , 32 , 37 ]. In harmony with the current results, a previous study suggested that reactive oxygen species (ROS) produced by TAA induce inflammation via the activation of Nuclear factor kappa B (NF-κB), which subsequently increased the release of downstream proinflammatory mediators such as IL-6 and TNF-α [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, Met, an inexpensive and broadly available medicine, has been shown to protect hepatocytes from oxidative stress-induced apoptosis in previous research [ 18 ]. Our study findings agree with previous data and also found that Met significantly decreased AST, ALT, ALP, GGT, total bilirubin, and direct bilirubin levels [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the best known substances with hepatotoxic effects are acetaminophen and ethanol [15]. There are studies that show the role of Met in the prevention of liver damage associated with the consumption of toxic substances [16][17][18].…”
Section: Introductionmentioning
confidence: 99%